A Comparative Study of Inheritance Law Systems in Malaysia and Brunei Darussalam: An Examination of Legal Dualism and Its Implementation in Muslim Communities - Awaluddinul Akbar , Muhammad; Wahyudin, Wahyudin; Darwis , Robi; Syahrul, Syahrul; Zuhra, Zuhra (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Background: Islamic inheritance law represents a critical component of family law systems that extends beyond religious obligations to encompass significant socio-economic implications for asset distribution and intergenerational justice. While Malaysia and Brunei Darussalam have both incorporated Islamic law into their national legal frameworks, their implementation approaches demonstrate fundamental structural and procedural differences that warrant systematic comparative analysis. Objective: This study examines the institutional frameworks and implementation effectiveness of Islamic inheritance law systems in Malaysia and Brunei Darussalam, analyzing how constitutional arrangements and governmental approaches influence the practical application of faraid principles. Methods: This research employs a normative legal methodology utilizing comparative analysis of legal frameworks, institutional structures, and judicial decisions. The study analyzes primary legal sources including constitutional provisions, statutory laws, court decisions, and administrative guidelines from both jurisdictions. Data collection encompassed library research examining fiqh literature, national legislation, official documents, scholarly articles, and religious legal opinions. Theoretical frameworks of legal pluralism (Romano-Gierke), Maqasid al-Shariah, and Hartian legal positivism provide analytical foundations for institutional effectiveness assessment. Results: Malaysia's dual legal system creates jurisdictional tensions between Syariah and civil courts, particularly regarding immovable property administration, resulting in administrative complexity and legal uncertainty that undermines Islamic law effectiveness. Conversely, Brunei's centralized Islamic legal framework demonstrates superior institutional coherence through exclusive Syariah court jurisdiction, enabling direct faraid implementation without inter-court conflicts. The study reveals that approximately RM42 billion in Muslim inheritance remains undistributed in Malaysia due to systematic administrative failures, while Brunei's unified approach achieves greater legal certainty and administrative efficiency. Conclusions: Institutional structures fundamentally determine Islamic inheritance law implementation effectiveness in contemporary Muslim societies. Successful Islamic law implementation requires comprehensive institutional support aligning legal structures with religious objectives rather than mere constitutional recognition. Malaysia's fragmented system inadvertently undermines Islamic law's divine authority through secular intervention, while Brunei's unified approach enhances religious legitimacy and community compliance.